2018
DOI: 10.1111/imj.13751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of limited English proficiency on presentation and outcomes of patients undergoing primary percutaneous coronary intervention for ST‐elevation myocardial infarction

Abstract: Doctor-patient language discordance has been shown to lead to worse clinical outcomes. In this study of patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction at an Australian health service, we demonstrated that limited English proficiency (LEP) is an independent predictor of prolonged symptom-to-door time, but does not lead to worse 30-day mortality compared with English-proficient patients. More effort needs to be placed in providing public health education in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Most (15/26 [57.7%]) studies were conducted in the USA, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with the remainder conducted in Australia and/or New Zealand, [27][28][29][30][31][32] or Canada [33][34][35][36][37] (Appendix 2). All USA-based studies were conducted in one of 5 states (California, 15,19,21,24,26 Massachusetts, 16,17,23,25 New Jersey, [12][13][14] New York, 20,22 or Minnesota 18 ).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most (15/26 [57.7%]) studies were conducted in the USA, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with the remainder conducted in Australia and/or New Zealand, [27][28][29][30][31][32] or Canada [33][34][35][36][37] (Appendix 2). All USA-based studies were conducted in one of 5 states (California, 15,19,21,24,26 Massachusetts, 16,17,23,25 New Jersey, [12][13][14] New York, 20,22 or Minnesota 18 ).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…31 Most studies included patients admitted with exclusively medical conditions or general hospital populations, though 4 focused on surgical conditions 13,14,17,36 and 1 focused on a procedural intervention. 28 Three studies examined the ICU setting 16,18,29 and 3 the ED setting. 22,23,26 All studies reported patient age and sex or gender, 12 included race and/or ethnicity, 9 included insurance type, and 9 included income status or a similar measure.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies, however, had wholly inaccurate definitions of language concordance, such as Mehler et al (31), who used patients' ethnicity and immigrant status as a proxy for limited English proficiency (LEP). Similarly, Biswas et al (21) defined LEP patients as any participant who did not self-report English as their primary language, negating the existence of multilingual participants. The majority of studies used self-reported surveys and questionnaires to collect data on preferred language and language fluency among patients and physicians, while other studies used electronic medical databases to access patients' primary language(s).…”
Section: Assessment Of Language Concordancementioning
confidence: 99%